Identity, community, and learning lives in the digital age - Erstad, Ola; Sefton-Green, Julian (Cambridge University Press, 2013)
Recent work on education, identity and community has expanded the intellectual boundaries of learning research. From home-based studies examining youth experiences with technology, to forms of entrepreneurial learning in informal settings, to communities of participation in the workplace, family, community, trade union and school, research has attempted to describe and theorize the meaning and nature of learning. Identity, Community, and Learning Lives in the Digital Age offers a systematic reflection on these studies, exploring how learning can be characterized across a range of 'whole-life' experiences. The volume brings together hitherto discrete and competing scholarly traditions: sociocultural analyses of learning, ethnographic literacy research, geo-spatial location studies, discourse analysis, comparative anthropological studies of education research and actor network theory. The contributions are united through a focus on the ways in which learning shapes lives in a digital age
Keywords: Gesellschaft; Learning / Social aspects; Educational sociology; Digital communications; Identity (Psychology); Psychosoziale Fähigkeit; Bildung; Lebensbewältigung; Lebenslanges Lernen; Lernumwelt; Psychosoziale Entwicklung; Aufsatzsammlung